PERANCANGAN DESAIN UI/UX APLIKASI MOBILE PADA SOLARIA RESTO DENGAN MENGGUNAKAN METODE LEAN UX - Yoga Setia Putra; Gito Resmi, Mochzen; Agus Sunandar, Muhamad (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
The rapid development of information technology encourages companies in various sectors to adopt mobile applications to improve customer experience and operational efficiency. Solaria, a leading fast food restaurant in Indonesia, needed to design an optimal user interface (UI) and user experience (UX) for its mobile application. This research aims to design the UI/UX of the Solaria app using the Lean UX method. The research method involves several stages: customer interviews and questionnaires to understand user needs, wireframes and initial prototypes, testing and iteration based on user feedback, and final evaluation of the refined prototype. The result of this research is a relevant and user-friendly design. This research is expected to serve as a reference for mobile application developers to be able to make a full application.